Perancangan Brand Komunikasi Untuk Mori Hampers Guna Meningkatkan Awareness Melalui Media Sosial - Angel Ang; Hutomo Setia Budi (Jurnal Vicidi, 2022)
Mori Hampers is a company engaged in the gift and delivery hampers are widely used for seasonal, birthday, wedding, etc. Mori Hampers was founded on April 11, 2020 in Mojokerto City. Mori Hampers has a target audience of Millennials aged 27-50 years and Generation Z with 17-26 years of age. So far, Mori Hampers has been promoting using Instagram feeds, stories and advertisements, just selling a product without the idea that communicating the values ​​of Mori Hampers is especially important for brand awareness. With this research, it aims to find out the right communication or promotion strategy to increase Mori Hampers Brand Awareness and Brand Communication in the intended target market. This study uses the Journal Literature Review method from various international and national journals and books in the last 10 years which discusses Brand Awareness, Brand Communication, Brand Identity, Marketing Strategy, Design Style and promotional objectives for Mori Hampers. Another method is the qualitative method by interviewing 3 Expert Users and 3 Extreme Users and quantitative in the form of surveys to people who are in accordance with the intended target market. The results of the study show that Brand Communication is very important to increase Brand Awareness in Mori Hampers. By improving Brand Communication, Mori Hampers can convey a Unique Value Proposition so that it can be well received by the target market. Keywords: Brand Communication, Brand Awareness, Brand Identity, Marketing Strategy, Design Style